Stability Analysis for Semi-Infinite Vector Optimization Problems under Functional Perturbations. (4th July 2022) - Peng, Zai-Yun; Zhao, Yun-Bin; Yiu, Ka Fai Cedric; Zhou, Ya-Cong
Abstract: This paper aims to study the stability of a class of semi-infinite vector optimization problems (SVOP) under functional perturbations. By using an important hypothesis H h ( p 0 ), a necessary and sufficient condition of Hausdorff continuity for weak efficient solution mappings and certain sufficient conditions for Painlevé-Kuratowski convergence of weak efficient solution sets for SVOP are established under the perturbations of both constraint sets and objective functions.